SLOW SPEED PHOTOGRAPHY AS A DROMOLOGICAL CRITIQUE OF LIFE - Rafli, Fauzan
This work explores the role of photography, particularly slow speed and multiexposure techniques, in representing the impact of acceleration culture on modern human behavior. In the fast-paced digital era, photography has become an integral tool in everyday life, influencing perceptions of time, identity, and ways of communicating. This work aims to investigate how photographic techniques can manipulate the temporal dimension and reveal the nuances of life experiences in an acceleration-oriented society. The research methodology combines practical and theoretical approaches. Analog photography techniques, particularly slow speed and multiple exposures are used in conjunction with old print processes to create a visual representation of the phenomenon under study. The analysis of the visual results is based on Paul Virilio's theory of dromology and the cultural concept of acceleration, which explores how speed affects human perception and experience. The research also investigates the auratic value of photography in the age of digital reproduction, with reference to the thoughts of Walter Benjamin, and analyzes how slow speed and multi-exposure techniques contribute to contemporary art discourse. By combining traditional photographic techniques and contemporary theories, this work aims to provide a deeper understanding of the intersection between technology, time, and aesthetic experience in the context of an accelerating culture. The outcome of this work is expected to provide new insights into the potential of photography as a medium to explore and represent the temporal aspects of human experience, as well as contribute to a broader discussion on the role of art in responding to and reflecting cultural change in the digital age. It also aims to broaden the understanding of photography as a contemporary art practice capable of responding to and offering critical perspectives on accelerating cultural phenomena. Furthermore, it seeks to provide an understanding of how we can take a wise stance in the face of acceleration, so that we can retain human values and maintain a balance between technological efficiency and the essence of profound life experiences.